Krajobraz miasta w narracji filmów dokumentalnych o Lublinie - Ziółkowska-Kurczuk, Natasza (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article is an attempt at a critical original analysis of documentary films in relation to the documentary and narrative function of the landscape. The author treats the film space as a ‘world picture’ as understood by Martin Heidegger, and in this context, she presents her own model of seeing and understanding the world present in her own documentary work. The landscape here is saturated with meanings, especially emptiness, lack and post-memory, which speaks the most in a metaphorical way about the non-existent world. The author also refers to Walter Benjamin’s concept of the city as a book, and reads the history of multicultural Lublin, a kind of ghost town, form this perspective. The article is therefore an original attempt to discover the mental layer of the film, which is usually beyond the reach of its recipient.